Original paperThe role of selectins in alopecia areata - Sudnik, Wiesława; Dańczak-Pazdrowska, Aleksandra; Silny, Wojciech; Osmola-Mańkowska, Agnieszka; Pazdrowski, Jakub; Polańska, Adriana (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : One of the main histopathological features of alopecia areata (AA) is a lymphocytic infiltration that surrounds hair follicles. Soluble forms of E, L, P-selectins are known indicators of ongoing inflammation. There are no studies regarding the assessment of their contribution in AA. Aim: To assess serum concentrations of selectins (E-selectin, L-selectin and P-selectin) in patients with AA in relation to selected clinical parameters, including disease severity and activity. Material and methods : Sixty-four patients with AA were involved in the study. The diagnosis was based on physical examination and photodermoscopy. The control group consisted of 40 healthy subjects. The serum concentrations of soluble E-selectin, L-selectin and P-selectin were detected with ELISA method. Results: Statistically significantly higher levels of E, P, L-selectins were found in AA patients as compared with the healthy group. Serum concentrations of soluble forms of E- and L-selectins correlated with the severity of the disease, while E-selectin with activity of AA. Conclusions : This study shows that selectins may play an important role in the pathogenesis of AA and may be a target of future therapies in this disease.